2015
DOI: 10.1103/physrevlett.115.010404
|View full text |Cite
|
Sign up to set email alerts
|

Robust Asymptotic Entanglement under Multipartite Collective Dephasing

Abstract: We derive an analytic solution for the ensemble-averaged collective dephasing dynamics of N noninteracting atoms in a fluctuating homogeneous external field. The obtained Kraus map is used to specify families of states whose entanglement properties are preserved at all times under arbitrary field orientations, even for states undergoing incoherent evolution. Our results apply to arbitrary spectral distributions of the field fluctuations.PACS numbers: 03.65. Yz, 03.65.Ud, 03.67.Mn Control of the coherent evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 41 publications
2
73
0
Order By: Relevance
“…Those obtained from the |Y ñ  states are then categorized as 'robust', while those from |F ñ  are 'fragile'. In fact, as we have shown above, only the Werner state (59) is robust under collective dephasing in any field direction, while the other Werner-like (64) states are robust only when a specific direction is chosen [15]. The preservation of entanglement within decoherence-free subspaces [46][47][48]-which in the present case, due to the absence of a Hamiltonian evolution, coincide with the above-mentioned time-invariant subspacesis a rather obvious phenomenon: if the state does not evolve in time, then its properties are naturally also conserved.…”
Section: Time-invariant States Versus Time-invariant Entanglementmentioning
confidence: 59%
See 3 more Smart Citations
“…Those obtained from the |Y ñ  states are then categorized as 'robust', while those from |F ñ  are 'fragile'. In fact, as we have shown above, only the Werner state (59) is robust under collective dephasing in any field direction, while the other Werner-like (64) states are robust only when a specific direction is chosen [15]. The preservation of entanglement within decoherence-free subspaces [46][47][48]-which in the present case, due to the absence of a Hamiltonian evolution, coincide with the above-mentioned time-invariant subspacesis a rather obvious phenomenon: if the state does not evolve in time, then its properties are naturally also conserved.…”
Section: Time-invariant States Versus Time-invariant Entanglementmentioning
confidence: 59%
“…Characterizing the intensity fluctuations with the probability distribution ( ) w p , the collective dephasing dynamics is described by In [15], the above integral was solved analytically without further assumptions, and in the following we will recall the resulting solution and some of its properties.…”
Section: Ensemble Average Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There, particular attention was paid to the existence and robustness of so called decoherence free sub-spaces (DFS) under collective dephasing [25]. Moreover, recent studies [28,29] have shown that collective dephasing could also be used as a resource to generate strong but separable correlations. We note that, due to their promise as a general passive strategy to protect quantum resources from noise, the study of DFS continues to be an active area of research, see [30] for a recent review on the theoretical aspects and [31] for experimental implementations.…”
mentioning
confidence: 99%